Analysis of the Influence of Job Satisfaction Mediation on the Relationship Between Knowledge Sharing and Organizational Culture on Employee Performance - Stanley Prabowo; Budi Eko Soetjipto; Ludi Wishnu Wardana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Improving how well employees perform is a key goal for companies in many different areas. This research looks into how the culture of an organization and the way knowledge is shared help achieve this goal, with a special focus on how job satisfaction plays a role in connecting these factors. The study used a quantitative approach, mainly through surveys and statistical analysis called SEM, to examine the links between these variables. The results show that having a strong organizational culture and good knowledge-sharing practices not only directly help improve performance but also do so indirectly by increasing job satisfaction. This means that job satisfaction acts as a partial bridge between these factors. Employees who are happy with their jobs tend to be more motivated to do their best, especially when they are in a supportive and collaborative environment and when the company has clear values. From a theoretical standpoint, this study provides deeper insights into the mental and social processes that affect how well employees perform. In practice, businesses can use these findings to create better policies. For instance, they can develop structured programs for managing knowledge, reinforce the company's core values, and improve aspects that affect job satisfaction like career growth and work-life balance. This research highlights the importance of taking a comprehensive approach to managing people, one that combines thinking, feeling, and social aspects. By improving these three areas—organizational culture, knowledge sharing, and job satisfaction—companies can build a work environment that is both productive and helps achieve long-term success for both employees and the organization.